Modeling the mechanisms of interest raising videos in education. Issue 5 (16th November 2021) - Wijnker, Winnifred; Bakker, Arthur; Schukajlow, Stanislaw; Drijvers, Paul
Abstract: The forced online education during the COVID pandemic in 2020 and 2021 showed many teachers how valuable video can be as a teaching tool. Videos have the potential to raise pupils' interest in educational content. The mechanisms of raising interest, however, have hardly been studied in actual materials used in actual classrooms. This study aims to validate the core components of a dynamic model (Film's Interest‐Raising Mechanisms [FIRM] model) that describes how pupils' interest in a video and the educational content is the result of their appraisals of video characteristics. The five appraisals in the model represent characteristics of learning materials and activities, of films and videos, and of games that have been found to potentially raise interest: Novelty and complexity, comprehensibility, complex developments, rewarding closure, and absorption. We empirically tested the use of four videos in six 12th‐grade science and mathematics classrooms (151 pupils) using pre‐ and post‐tests, and path‐modeling. All five appraisals in the FIRM model were found to be significant predictors for the pupils' interest in the video and for their development of interest in the educational content. Abstract :